Uwarunkowania sytuacyjno-organizacyjne wdrażania organizacji procesowej - Kraśniak, Janusz (Situational and Organizational Factors of the Implementation of Process Organization, 2009)
The article presents the concept of process-oriented organization and some conclusions of the research. The factors that determine the effectiveness of process organization were identified as the following: the size of the enterprise, the level of using the information technology, the identification of customers, the correct identification of the process course. The centralization of decision-making, permanent character of process teams (quality), management opposition against organization change and level of the management background are the barriers of the implementation of process organization.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 389-395